Gestão social dos mandatos coletivos no Brasil à luz da democracia deliberativa - Avelar, Samara Aparecida Resende (2021)
In this research, we made a qualitative multi-case study to analyze how the pioneering collective mandates in Brazil – Collective Mandate Alto Paraíso and “Muitas-Gabinetona”– developed their management models and used deliberation in their decision-making processes during the legislature from 2017 to 2020. We based the definition of the study universe on the typology proposed by Secchi et al. (2019) for models of collective and shared mandates, and in which initiatives defined as “collective mandates” figure at the most decentralized level of political-administrative management. For the analysis, we used the Theory of Communicative Action by Jürgen Habermas, which is the basis for the concepts of Deliberative Democracy and Social Management. For the methodological reference, we took the criteria already defined in the scientific literature for the analysis of deliberative citizenship - which are a process of discussion, inclusion, pluralism, autonomy, participatory equality, and the common good - as well as its correlation with theoretical categories of social management. We conduct the study through documentary research: news published in the press on the subject, opinion articles published by key actors, bills filed in the Legislative, as well as posts and texts published on Facebook pages and websites of collective mandates. As a way of contextualizing the phenomenon, we present discussions that indicate weaknesses in the representative democratic model and the emergence of new formats of political representation in the world. As methodological perspectives for the analysis of deliberative citizenship criteria, we used “Content Analysis” - which enabled the thematic categorization of the collected texts - and the “Critical Discourse Analysis”, reconciling procedures proposed by Fairclough and Van Dijk for the analysis of the information clarity aspect. The investigation showed that the initiatives promoted management models in tune with the analytical categories of deliberative citizenship and with the principles of deliberative democracy and social management. The collective mandates practiced dialogic processes with citizens in decision-making, whether for the application of resources from parliamentary activities, or for the elaboration of normative contents. The groups also developed instruments to prepare the society to draw bills of popular initiative and to encourage citizen participation and the occupation of institutional policy, enabling actors previously excluded from the debate on public policies to mobilize and transform aspects of the society. However, the work also showed that the capacity of intervention of these initiatives is limited for the dynamics of the legislative chambers: projects elaborated through wide public debate were rejected, or are still in progress, or even were shelved at the end of the first legislature due to the length of parliamentary processes. In this sense, the public mobilization can be understood as the most important requirement to influence the parliamentary body and to achieve the objectives of social actors within the scope of public policies. The innovative instruments and actions of the collective mandates raised in this work can be used by other groups interested in developing collective candidacies, adapted to local specificities and improvements in the processes.